Analisis Penurunan Parameter Limbah Cair Laundry Menggunakan Rotating Biological Contactor (Rbc) - Nurdwi Sartika; Monik Kasman; Anggrika Riyanti (Universitas Batanghari Jambi, 2019)
Laundry waste water is a part of domestic liquid waste and its classified as grey water. Liquid waste from laundry business containing pollutants such as BOD, COD, TSS, Total Phosphate, and Methylene Blue Active Substance (MBAS) that can give negative impact to the environment if it is not treated first. The purpose in this study was to analyze the influence of detention time to eficiency of decreasing pollutant concentration by using Rotating Biological Contactor (RBC) methods. The RBC used the palm fiber as the media. Variation of detention time in this study was 1, 3, 5, 7, 9, 11, 13, and 15 days. Linear regression was used to analysed the effect of detention time to pollutant concentration decreased. The result showed that the elimination efficiency of BOD, COD, TSS, Total phosphate and MBAS was 88%, 87%, 87%, 88% and 96%. The regression analysis results showed that there was a significant relationship between detention time and efficiency of decreasing pollutant parameters concentration (BOD, COD, TSS, Total Phosphates) of laundry waste by using RBC, but has no significant relationship in MBAS parameter.